Analisis Financial Distress Menggunakan Metode Altman Z-Score Pada PT Sepatu Bata Tbk Periode 2021-2023 - Nadia Usman; Dirga Yunita, Beatriks; Nurul Falah Islami; Komang Tri Kusuma Ningsih; Rafiqah Asaff; Arini Lestari Aris (LPPM STIEM BONGAYA, 2024)
PT Sepatu Bata Tbk is one of the companies listed on the IDX which is engaged in the footwear industry and produces various types of leather shoes and sandals. The company's finances began to deteriorate in 2020, and continues to this day. In its latest financial report, Bata posted losses for four consecutive years. The research objectives to be achieved in this study are to determine the analysis of the level of bankruptcy using the Altman Z-Score method at PT Sepatu Bata Tbk for the 2021-2023 period. The analysis technique used in this study is to use the Altman Z-Score model. in 2021 a Z-Score value of 2.55 was obtained. With an assessment criterion of 1.81 < 2.55 < 2.99, which means that PT Sepatu Bata Tbk is in the gray area category. From this study, it was found that in 2022, a Z-score value of 1.64 was obtained with an assessment criterion of 1.64 < 1.81, which means that PT Sepatu Bata Tbk is in the bankrupt category. While in 2023, a Z-score value of 0.48 was obtained with an assessment criterion of 0.48 < 1.81, which means that PT Sepatu Bata Tbk is in the bankrupt category. PT Sepatu Bata Tbk in 2021 has an X1 ratio of 0.1815. In 2022 the value of the X1 ratio of PT Sepatu Bata Tbk decreased, namely 0.0121. Then in 2023 the X1 ratio value decreased again, namely -0.0847. The decrease in the X1 ratio value of PT Sepatu Bata Tbk every year is caused by the unstable value of current assets, current debt, and total assets of PT Sepatu Bata Tbk. Ratio X3 of PT Sepatu Bata Tbk in 2021 has a value of -0.297. In 2022 the X3 ratio also has a value of -0.09. In 2023 the value of the X3 ratio of PT Sepatu Bata Tbk decreased, namely -0.27. The minus value in the X3 ratio of PT Sepatu Bata is because the company suffered losses in those 3 years. From the research it can be concluded that PT Sepatu Bata Tbk for the period 2021-2023 using the Altman Z-score model, the results obtained in 2021 PT Sepatu Bata Tbk is in a gray area, which means that the company is in an unhealthy financial condition and is not bankrupt either. Meanwhile, in 2022 and 2023 PT. Sepatu Bata Tbk is in bankrupt condition, which means that the company's financial condition is not healthy